OPTIMISM IN FACING RETIREMENT FOR TNI AND POLRI SOLDIERS - Wulandari, Wenny; Rahmawan , Wise (International Journal of Social Science, 2024)
Working individuals consider retirement as a break from routine activities that have been carried out for years. Therefore, many individuals identify retirement as a scary thing, where the work routine they have been carrying out must be stopped, besides that the income they earn starts to decline, and the authority they had while actively working is lost. This research aims to find out a picture of optimism in facing retirement among TNI and POLRI soldiers. The subjects in this research were TNI and POLRI soldiers. The scale used in this research is optimism. The data analysis method used in this research is descriptive statistical analysis. The results obtained in this study show that the empirical mean (ME) of the optimism scale is 134.8, which indicates that the respondents have high optimism. Based on these results, it can be concluded in general that optimism in facing retirement among TNI and POLRI soldiers tends to be high